Physicochemical and Biological Characterization of Ti6Al4V Particles Obtained by Implantoplasty: An In Vitro Study. Part I - Jorge Toledano-Serrabona (MDPI AG, 2021)
Implantoplasty is a mechanical decontamination technique that consists of polishing the supra-osseous component of the dental implant with peri-implantitis. This technique releases metal particles in the form of metal swarf and dust into the peri-implant environment. In the present in vitro study, the following physicochemical characterization tests were carried out: specific surface area, granulometry, contact angle, crystalline structure, morphology, and ion release. Besides, cytotoxicity was in turn evaluated by determining the fibroblastic and osteoblastic cell viability. As a result, the metal debris obtained by implantoplasty presented an equivalent diameter value of 159 µm (range 6–1850 µm) and a specific surface area of 0.3 m2/g on average. The particle had a plate-like shape of different sizes. The release of vanadium ions in Hank’s solution at 37 °C showed no signs of stabilization and was greater than that of titanium and aluminum ions, which means that the alloy suffers from a degradation. The particles exhibited cytotoxic effects upon human osteoblastic and fibroblastic cells in the whole extract. In conclusion, metal debris released by implantoplasty showed different sizes, surface structures and shapes. Vanadium ion levels were higher than that those of the other metal ions, and cell viability assays showed that these particles produce a significant loss of cytocompatibility on osteoblasts and fibroblasts, which means that the main cells of the peri-implant tissues might be injured.